Low-Dose Pulsatile Interleukin-6 As a Treatment Option for Diabetic Peripheral Neuropathy - Cox, April Ann; Sagot, Yves; Hedou, Gael; Grek, Christina; Wilkes, Travis; Vinik, Aaron I.; Ghatnekar, Gautam (Frontiers in Endocrinology, 2017)
Diabetic peripheral neuropathy (DPN) remains one of the most common and serious complications of diabetes. Currently, pharmacological agents are limited to treating the pain associated with DPN, and do not address the underlying pathological mechanisms driving nerve damage, thus leaving a significant unmet medical need. Interestingly, research conducted using exercise as a treatment for DPN has revealed interleukin-6 (IL-6) signaling to be associated with many positive benefits such as: enhanced blood flow and lipid metabolism, decreased chronic inflammation, and peripheral nerve fiber regeneration. IL-6, once known solely as a pro-inflammatory cytokine, is now understood to signal as a multifunctional cytokine, capable of eliciting both pro- and anti-inflammatory responses in a context dependent fashion. IL-6 released from muscle in response to exercise signals as a myokine and as such has a unique kinetic profile, whereby levels are transiently elevated up to 100 fold and return to baseline levels within 4 hrs. Importantly, this kinetic profile is in stark contrast to long-term IL-6 elevation that is associated with pro-inflammatory states. Given exercise induces IL-6 myokine signaling, and exercise has been shown to elicit numerous beneficial effects for the treatment of DPN, a causal link has been suggested. Here, we discuss both the clinical and preclinical literature related to the application of IL-6 as a treatment strategy for DPN. In addition, we discuss how IL-6 may directly modulate Schwann and nerve cells to explore a mechanistic understanding of how this treatment elicits a neuroprotective and/or regenerative response. Collectively, studies suggest that IL-6, when administered in a low-dose pulsatile strategy to mimic the body’s natural response to exercise, may prove to be an effective treatment for the protection and/or restoration of peripheral nerve function in DPN. This review highlights the studies supporting this assertion and provides rationale for continued investigation of IL-6 for the treatment of DPN.